Interest Rate Liberalization and Commercial Bank Performance: New Evidence From Chinese A-Share Banks - Dilesha Nawadali Rathnayake; Yang Bai; Pierre Axel Louembé; Li Qi (SAGE Open, 2022)
Abundant literature infers the negative incidence of financial liberalization in the banking sector. As interest rate marketization is a reality in China, we empirically investigate the determinants of commercial banks’ financial performance using 10 listed Chinese commercial banks for 1999 to 2019. Our findings suggest that net interest margin (NIM), non-performing loans (NPL), and asset size (LnAsset) are the key drivers of profitability in Chinese banks. Interestingly, for the sample of city banks observed, we find that bank performance is strongly driven by sound management of the assets and the retail interest margins. On the opposite, the joint-stock banks’ strong diversification leads to lower reliance on net interest margins. Our results also suggest that joint-stock banks’ asset size puts strong pressure on their overall performance and exert a diminishing return effect as their assets’ critical size generates proportional administrative expenses that hinder profitability.